Contemporary Factors Influencing Integration of Pupils with Special Needs in Public Primary Schools in Eldoret Municipality, Kenya - Lusweti M. , Pamela; Kisilu , Anne Kisilu; Nyandusi, Charles (African Journal of Education,Science and Technology (AJEST), 2014)
One of Kenya‟s Vision 2030 strategies is to enforce Children‟s Act which is meant to eliminate child labour as well as other retrogressive practices causing vulnerabilities among children and thus integration is inevitable. This study aimed at investigating school factors currently influencing integration of learners with special needs (SNE) in public primary schools in Eldoret Municipality, Kenya. The objectives were to investigate whether teachers‟ familiarity with SNE curriculum and availability of resources and facilities influenced integration of learners with special needs. It adopted a descriptive survey research design. Sampling involved 19 head teachers and 800 teachers from the 39 public schools. Stratified method of sampling was used to automatically include head teachers of selected schools in the study and simple random sampling to select 259 teachers to ensure sub groups were proportionately represented. The questionnaire was used to collect data from teachers and an interview schedule for head teachers. Descriptive statistics were employed in analyzing data using frequencies and percentages to meaningfully describe the distribution of scores and data were analyzed using SPSS. The results showed that 81% of the teachers in the municipal public primary schools were familiar with, and used the ordinary curriculum as opposed to a differentiated one which is special-needs friendly. SNE teachers, physical facilities and resources in the schools were either unavailable or inadequate.